Neurospora crassa cytoplasmic ribosomes; ribosomal ribonucleic acid synthesis in the wild type. - Russell, P J (1976)
The biosynthesis of ribosomal ribonucleic acid (rRNA) In wild-type Neurospora crassa growing at 25 degrees C was investigated by continuous-labeling and pulsechase experiments using [5-3H]uridine. The results of these experiments suggest the following precursor-product relationships: the first RNA molecule to be synthesized in significant quantities is the 2.4 X 10(6)-dalton (2.4-Mdal) ribosomal precursor RNA. This RNA is cleaved to produce two species of RNA with weights of 0.7 and 1.4-Mdal. The former is the mature 17S rRNA of the 37S ribosomal subunit. The 1.4-Mdal RNA is subsequently cleaved to produce the mature 1.27-Mdal (25S) and 61,000-dalton (5.8S) rRNA's of the 60S ribosomal subunit. In the maturation process, approximately 15 to 20% of the 2.4-Mdal ribosomal precursor rRNA molecule is lost. As in other eukaryotes that have been examined, 5S rRNA is not derived from this precursor molecule.